Whither pertussis? - Snelling, Thomas; Waddington, C. (Expert Reviews Ltd., 2015)
© 2015 Informa UK, Ltd. Several lines of evidence suggest that pertussis disease will continue to rise in countries which have switched to acellular vaccines. While maternal vaccination is promising as a mitigating strategy it is unlikely to replace the need for a better vaccine. In the absence of a clear alternative, a return to using whole cell vaccines, at least in part, should not be dismissed as an option without contemporary studies of feasibility and acceptability.